Denoising and semantic segmentation of 4D datasets with undersampled micro X-ray CTs using deep learning - Bellos, Dimitrios (2021)
Over recent years, multiple imaging approaches has been proposed to depict the hidden inner structure of many different biological and non-biological systems in the form of 3D volumes. As time progressed due to multiple technological advances, these methods have become faster and more accessible, allowing in recent years the collection of time-resolved volumes that form 4D datasets. With 4D capturing techniques, the hidden inner structure of a system is collected repeatedly through time, allowing us to perceive not only its 3D structure, but temporal changes of this structure. Nevertheless, despite the technological advances in data collection there is still a major need for accurate, efficient and easy to use methods for 3D and 4D data analysis.